6x+6x+3x+49=96x+3x+x

Simple and best practice solution for 6x+6x+3x+49=96x+3x+x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+6x+3x+49=96x+3x+x equation:


Simplifying
6x + 6x + 3x + 49 = 96x + 3x + x

Reorder the terms:
49 + 6x + 6x + 3x = 96x + 3x + x

Combine like terms: 6x + 6x = 12x
49 + 12x + 3x = 96x + 3x + x

Combine like terms: 12x + 3x = 15x
49 + 15x = 96x + 3x + x

Combine like terms: 96x + 3x = 99x
49 + 15x = 99x + x

Combine like terms: 99x + x = 100x
49 + 15x = 100x

Solving
49 + 15x = 100x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-100x' to each side of the equation.
49 + 15x + -100x = 100x + -100x

Combine like terms: 15x + -100x = -85x
49 + -85x = 100x + -100x

Combine like terms: 100x + -100x = 0
49 + -85x = 0

Add '-49' to each side of the equation.
49 + -49 + -85x = 0 + -49

Combine like terms: 49 + -49 = 0
0 + -85x = 0 + -49
-85x = 0 + -49

Combine like terms: 0 + -49 = -49
-85x = -49

Divide each side by '-85'.
x = 0.5764705882

Simplifying
x = 0.5764705882

See similar equations:

| 14k+8k+88=163 | | 25=4a+19 | | y=x2−2x+48x+y=20 | | 0.04(4c-80)=-0.8(C-2) | | 2x+10-x=2(2x-6) | | 13-x=x^2+1 | | 73=0.7-4 | | 32=4a+19 | | 8(s-92)=32 | | 4(2)+3(-3)=-1 | | kx^2-36x=36 | | 1-(3/2-5x)=-2/5-2x | | 94y^2+56y=0 | | -3x-9=20-4x | | -128=4(4-6x) | | -5x+3-7x-1= | | 16+4h=36 | | -1(-6x+3)=9 | | 5000=x/706.85 | | 1.5/2.5=3/x | | 5000=x/(225π) | | (7n-35)(5n-4)=0 | | 5ix+3x= | | 3ix+5x= | | -m-1=6m+9 | | 1/2*p=377 | | 4x-10=6x+4 | | X-0.1X=320595 | | 13+y=16+13 | | X^2+10x-84=180 | | 2y=4*2-2 | | 2y=4*5-2 |

Equations solver categories